2008
DOI: 10.1016/j.ssnmr.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Study of molecular dynamics and cross relaxation in tetramethylammonium hexafluorophosphate (CH3)4NPF6 by 1H and 19F NMR

Abstract: a b s t r a c t (CH 3 ) 4 NPF 6 is studied by NMR measurements to understand the internal motions and cross relaxation mechanism between the heterogeneous nuclei. The spin lattice relaxation times (T 1 ) are measured for F NMR results are attributed to cross relaxation between proton and fluorine and motional parameters for the PF 6 group reorientation are evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Several authors have observed a similar behavior in a number of compounds, for example, Watton et al [22] in (NH 4 ) 2 TiF 6 and McDowell et al [34] in (CH 3 ) 3 NPF 5 , and have explained their results in a similar manner. We have recently [35] observed a similar cross relaxation between 1 H and 19 F in (CH 3 ) 4 NPF 6 . Indeed, in the present compound, Kavun et al [11] have also observed that the 19 F second moment reaches the rigid lattice limit at a much higher temperature of about 250 K. Figure 4 shows fitting of Eq.…”
Section: Analysis Of 19 F Nmr Tsupporting
confidence: 62%
“…Several authors have observed a similar behavior in a number of compounds, for example, Watton et al [22] in (NH 4 ) 2 TiF 6 and McDowell et al [34] in (CH 3 ) 3 NPF 5 , and have explained their results in a similar manner. We have recently [35] observed a similar cross relaxation between 1 H and 19 F in (CH 3 ) 4 NPF 6 . Indeed, in the present compound, Kavun et al [11] have also observed that the 19 F second moment reaches the rigid lattice limit at a much higher temperature of about 250 K. Figure 4 shows fitting of Eq.…”
Section: Analysis Of 19 F Nmr Tsupporting
confidence: 62%
“…The dynamical behavior of the constituent ions is central in controlling the physical state and properties of these materials. Therefore, a fundamental mechanistic understanding of the PF 6 – rotational dynamics in the solid state for alkali salts, ammonium salts, and the other complex salts has been the subject of intense investigation in the literature. As might be expected, the PF 6 – rotational dynamics depend on temperature as well as on the chemistry, structure, and phase state of the material in question.…”
Section: Introductionmentioning
confidence: 99%
“…68 It is intuitively expected and was suggested in a number of previous studies that the ionic volume or radius is roughly correlated with PF 6 − rotational dynamics. 2,5,14,23 This is because larger ionic volume can decrease cation−anion interaction that could result in faster PF 6 − rotational dynamics. However, the data in Figure 6 indicate almost no relationship between the ionic volume and the dynamical parameters for the PF 6 − rotational dynamics.…”
mentioning
confidence: 99%